Electrical bistability in MoS2 nano-sheets doped polymeric nanocomposite films. (2020) - Pathak, Prashanta; Deb, Rajesh; Mohapatra, Saumya R.
Abstract: Herein, we report the preparation and characterisation of nanocomposite films comprised of poly(ethylene oxide) (PEO) dispersed with exfoliated MoS2 nano-sheets. Few-layer nano-sheets of MoS2 with good stability and yield were prepared using liquid phase exfoliation method. Optical spectroscopic techniques and atomic force microscopy confirm exfoliation of MoS2 into few-layer nano-sheets. The current-voltage characteristics were investigated on two terminal devices by putting composite of PEO and MoS2 nano-sheets as the active material between ITO and aluminium electrodes. Electrical bistability observed with low resistance state (LRS) and high resistance states (HRS) were reversibly achieved by voltage sweeping. LRS (ON) and HRS (OFF) occurred at -3.5 V and 2 V respectively when the compliance was set at 50 µA. The resistance-ratio (Roff /Ron ) ∼ 10 4 is achieved where the switching between resistance states is due to trap assisted space-charge limited current